RP1, a RAGE antagonist peptide, can improve memory impairment and reduce Aβ plaque load in the APP/PS1 mouse model of Alzheimer's disease. (1st December 2020) - Huang, Yi-yun; Fang, Nian; Luo, Hui-ru; Gao, Feng; Zou, Yao; Zhou, Li-li; Zeng, Qing-ping; Fang, Shi-song; Xiao, Fei; Zheng, Qing
Abstract: Amyloid-β (Aβ) accumulation is a pathological hallmark of Alzheimer's disease (AD). The receptor for advanced glycation end products (RAGE) is involved in the production and accumulation of Aβ. RP1, a peptide antagonist of RAGE, was screened by phage display technology in our previous studies, and its neuroprotective effects on an AD cell model have been confirmed. However, its efficacy in vivo remains unclear. Here, the intranasal delivery of RP1 to APPSwe/PS1dE9 (APP/PS1) mice significantly improved memory impairment and relieved the Aβ burden by decreasing the expression of amyloid precursor protein and β-secretase. RNA-sequencing (RNA-seq) was utilized to identify differentially expressed genes (DEGs) in APP/PS1 mice after RP1 administration. Several DEGs in RAGE downstream signalling pathways were downregulated. Some transcription factors (such as Fos) and the pathways enriched in the remarkable modules may also be related to the efficacy of RP1. In conclusion, RP1 significantly improves the AD symptoms of APP/PS1 mice, and the RNA-seq results provide new ideas for elucidating the possible mechanisms of RP1 treatment. Highlights: Nasal delivery of RP1 to APP/PS1 mice significantly improved their memory deficits. RP1 decreased Aβ accumulation by reducing APP and BACE1 in the brains of AD mice. RP1 treatment downregulated several DEGs in RAGE downstream signalling pathways. The transcription factors like Fos may play a role in RP1 treatment. Some pathways like Cholinergic synapse pathway may be related to RP1 treatment.